Bio-oil production from waste potato peel and rice hush - Batista, Marcelo da Silva; Guimarães, Camila Oliveira; Marra, Lívia Carneiro; Maloncy, Maikel Laurence (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Pyrolysis is one of the most effective, economic and useful ways to produce bio-oil in the absence of oxygen. This article presents a study about the production of bio-oil from pyrolysis of waste potato peel and rice husk.This study aimed to evaluate the influence of the average particle size of the waste potato peel, and compare the results with another raw material, the rice husk. Three particles size were analyzed: (a) 0,500<Ø<1,400 mm, (b) 1,400<Ø<3,350 mm, and (c) Ø>3,350 mm. The best result with liquid (water and bio-oil) was 29.18% and it was obtained from the smaller particle size. The results obtained from potato peel and rice husk were compared for grain sizes (a) and (b). It was observed that the rice husk with the smaller size is more effective for bio-oil production (44.29% of liquid). However for the large particles sizes, the most effective raw material was the potato peel presenting a result of 27.74% of liquid